Critical AI Literacy in Arabic Language Education: Rethinking Teacher Roles, Ethics, and Curriculum in the Age of Generative AI - Muhammad Fariq Heemal Attruk; Nik Hanan Mustapha (Global Education Journal, 2026)
This study examines the growing role of generative artificial intelligence (AI) in Arabic language education and highlights the increasing need for critical AI literacy among learners and teachers. While AI tools offer opportunities to support grammar learning, vocabulary development, writing practice, and independent learning, concerns remain regarding accuracy, overreliance, academic integrity, and the decline of critical thinking. The study aims to explore the need for critical AI literacy in Arabic language learning, examine the changing role of teachers, identify institutional and ethical challenges, and propose a conceptual framework for future practice and research. A Narrative Literature Review (NLR) approach was employed to synthesize and critically interpret relevant studies. Literature was collected from Scopus and Google Scholar, resulting in 26 primary studies that were analyzed through thematic synthesis. The review identified six major themes: critical AI literacy as a pedagogical necessity, the repositioning of teachers, infrastructure and policy challenges, academic ethics and integrity, teacher professional development and AI-responsive curriculum design, and the development of a critical AI literacy framework. Based on these findings, the study proposes a preliminary framework consisting of evaluative linguistic skills, awareness of AI limitations, human–AI collaboration, the use of morphology-aware and adaptive AI tools, and the integration of digital technologies with sound pedagogical practices. The study concludes that effective AI integration in Arabic language education requires critical engagement, informed human judgment, teacher preparedness, and context-sensitive educational policies.